Wawasan Bibliometrik tentang Strategi Pemasaran Digital untuk Kampanye Politik di Indonesia - Kaaamiliaa Dewi; Dian Eka Rahmawati; Muhammad Younus; Muhammad Ridha (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2026)
This study aims to examine in depth the influence of digital marketing in political campaigns in Indonesia. This research departs from the gap between the theoretical potential of digital marketing, widely discussed in the global literature, and its empirical application, which remains limited in the Indonesian political context. The contemporary political dynamics in Indonesia an increasingly dependent on information technology and social media, making this study both relevant and urgent. The research method uses qualitative bibliometric analysis with primary data obtained from the Scopus database. The data were processed in RStudio and filtered according to the PRISMA protocol, yielding 58 journal articles that were systematically analyzed. The results show that digital marketing strategies, particularly through social media, data-driven micro-targeting, and creative content, have shifted the paradigm of political campaigns from traditional approaches to more personalized, interactive, and measurable interactions. The trend analysis also reveals the evolution of research focus, from the initial platform adoption stage to more complex strategies, involving artificial intelligence, digital ethical issues, and platform governance. The study concludes that digital marketing has transformed the Indonesian political campaign landscape, making in more dynamic. However, its effectiveness still requires support in the form of increasing people’s digital literacy, protective regulations, and follow-up research using a mixed-methods approach to empirically measure causal impacts. This research contributes to the development of digital political marketing literature while providing practical implications for political actors and policymakers in Indonesia.